2020
DOI: 10.1002/ncp.10548
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerance of Enteral Nutrition in the Medical and Surgical Intensive Care Unit Patient Receiving Vasopressors

Abstract: Background Multiple societal guidelines recommend enteral nutrition (EN) be initiated within 24 to 48 hours of admission to the intensive care unit (ICU) once a patient is hemodynamically stable. Gastrointestinal intolerance and occurrence of bowel ischemia have been a concern for patients receiving vasopressors while concurrently receiving luminal nutrients. The study objective was to determine whether patients receiving vasopressors while concomitantly receiving enteral nutrients had more incidences of bowel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…The HRNSP specified the use of the vasopressor agent epinephrine because of its first‐line use in our CVICU for cardiogenic shock, cardiopulmonary resuscitation, cardiac arrest, and low CO after cardiac surgery 67 . To date, most studies investigating EN tolerance and vasopressor therapy target MICU/SICU patient populations with septic shock and norepinephrine or equivalent dosing 68,69 . Norepinephrine equivalent dosing is expressed as a sum of all vasopressors with 1 mg of epinephrine equivalent to 1 mg of norepinephrine, 70 suggesting these two agents exert equivalent splanchnic vasoconstricting effects at all dose ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRNSP specified the use of the vasopressor agent epinephrine because of its first‐line use in our CVICU for cardiogenic shock, cardiopulmonary resuscitation, cardiac arrest, and low CO after cardiac surgery 67 . To date, most studies investigating EN tolerance and vasopressor therapy target MICU/SICU patient populations with septic shock and norepinephrine or equivalent dosing 68,69 . Norepinephrine equivalent dosing is expressed as a sum of all vasopressors with 1 mg of epinephrine equivalent to 1 mg of norepinephrine, 70 suggesting these two agents exert equivalent splanchnic vasoconstricting effects at all dose ranges.…”
Section: Discussionmentioning
confidence: 99%
“…67 To date, most studies investigating EN tolerance and vasopressor therapy target MICU/SICU patient populations with septic shock and norepinephrine or equivalent dosing. 68,69 Norepinephrine equivalent dosing is expressed as a sum of all vasopressors with 1 mg of epinephrine equivalent to 1 mg of norepinephrine, 70 suggesting these two agents exert equivalent splanchnic vasoconstricting effects at all dose ranges.…”
Section: Vasopressor Agentmentioning
confidence: 99%
“…A retrospective study ( N = 120) of enteral tolerability in MICU patients with septic shock receiving vasopressor support found that a GRV >250 ml was the most common reason for enteral intolerance; 74% of those with enteral intolerance had a GRV >250 ml (34 of 46) 8 . In a 2020 study by Sabino et al, GRVs >300 ml were almost three times more likely in those receiving EN and vasopressors ( N = 178) when compared with those only receiving EN ( N = 141) (20% vs 7%; P < 0.01) 7 . Professional societies differ in opinion regarding GRVs.…”
Section: Timing Of Enmentioning
confidence: 97%
“…However, once adjusted for confounders, statistical significance between lactate and EN tolerance was not maintained 1 . Recent case studies by Sabino et al also demonstrate that serum lactate levels are inconsistent before the onset of bowel ischemia and point out that elevations may be a delayed response to an existing ischemic bowel 7 . At this time, there are insufficient data to support utilizing lactate as a monitoring parameter.…”
Section: Timing Of Enmentioning
confidence: 99%
“…26 Other observational studies, not exclusively in septic shock patients, noted safety, tolerance, and associated improved clinical outcomes with EN in circulatory shock. [28][29][30][31][32][33] In a large observational study evaluating outcomes of mechanically ventilated patients with circulatory shock receiving early vs late EN, Ohbe et al found bowel ischemia occurred in 21 of 8606 (0.2%) patients who received early EN and 50 of 17,216 (0.3%) patients who received late EN. 34 Approximately one-third of patients had septic shock.…”
Section: What Is the Clinical Evidence For Initiating En In Septic Shock?mentioning
confidence: 99%